The Definition, Assessment, and Treatment of Allodynia of the Hand: An International Delphi Study - Hebert, Andrea (My University, 2022)
Introduction Allodynia is a type of neuropathic pain defined as pain due to a stimulus which does not normally provoke pain. There is little research and conflicting advice. The purpose of this thesis is to provide a summary of the current state of hand therapy knowledge. To accomplish this, a review of the hand therapy literature related to allodynia was conducted, along with the collection of expert opinion utilizing the Delphi survey technique. Methods International hand therapy experts were invited to participate in a classical Delphi study. Mixed methods were used to summarize each round and inform any subsequent questioning. Thematic analysis was used to look for patterns of meaning within the written responses. A consensus level of 75% was decided upon a priori for all final recommendations. Results Forty-three hand therapists from 15 countries contributed to the fourth and final round. Through the consensus process definitions related to allodynia, and assessments and treatments for allodynia, were explored and recommendations generated. Two themes were identified 1) assessment and treatment decisions depend on the client’s presumed underlying mechanisms contributing to the allodynia as well as psychosocial and functional status, and 2) whether the area of allodynia should be touched or not. Discussion and conclusions The literature and our survey results are mixed on whether it is beneficial to touch an area of allodynia. Other aspects related to allodynia such as functional or psychosocial impact are rarely addressed in the literature but were highlighted in our survey. This thesis contributes to the knowledge by presenting: 1) a summary of the current literature, 2) a new consensus definition of hypersensitivity, 3) experts’ recommendations for assessment and treatment of allodynia of the hand and factors to consider when utilizing these, and 4) recommendations for future research, practice, and education.
Keywords: Allodynia, Hand Therapy, Desensitization, Somatosensory Rehabilitation of Pain, Delphi